Recurrent lymphangioma after two operations. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Lymphangioma (L) is a localized malformation of lymphatic vessels, which is not connected with the normal lymphatic circulation. There are superficial L, consisting of cystic, 1-3 mm in diameter cavities containing serum or blood liquid and deep L, consisting of larger and deeper cavities, which usually get evident due to an intralesional hemorrhage. There are not clear-cut limits between these two entities, as the case here reported shows, with appearance of superficial L after removal of deep L. Cystic hygroma is a very large L (2) often present at birth on the neck. The surgical removal of L is often followed by recurrence (1). Intralesional sclerosing agents as OK432 can be useful in very large lymphangiomas.